Low-Power SAR ADCs: Basic Techniques and Trends - Pieter Harpe (IEEE Open Journal of the Solid-State Circuits Society, 2022)
With the advent of small, battery-powered devices, power efficiency has become of paramount importance. For analog-to-digital converters (ADCs), the successive approximation register (SAR) architecture plays a prominent role thanks to its ability to combine power efficiency with a simple architecture, a broad application scope, and technology portability. In this review article, the basic design challenges for low-power SAR ADCs are summarized and several design techniques are illustrated. Furthermore, the limitations of SAR ADCs are outlined and hybrid architecture trends, such as noise-shaping SAR ADCs and pipelined SAR ADCs, are briefly introduced and clarified with examples.